Forests and food security: a review - Sunderland, T.C.H.; O’Connor, A. (CAB International, 2020)
Forests are the largest source of terrestrial biodiversity and contain over half of the world’s terrestrial plant and animal species. In addition to the multitude of species supported by forest systems, forests are also responsible for life-sustaining ecological processes such as nutrient cycling and water regulation. As a rich source of plants, animals, soil, and water, the connection between forests and food seems undeniable. However, until recently, this relationship has been poorly understood. In this review, we explore three main pathways in which forests contribute to food security and nutrition. These include: (1) a direct consumption pathway, (2) an income pathway and (3) an agroecological pathway. We find the following: (1) forests contribute directly to people’s diets through the harvest of bushmeat, wild fruits and other forest-sourced foods; (2) the sale of non-timber forest products contribute to people’s income, enabling the purchase of a diversity of food items from markets; and finally (3) forests and trees support diverse crop and livestock production through an array of ecosystem services such as pollination, soil fertility and water and climate regulation. Our findings shed light on the vital role that forests play in food security and we conclude that further research is needed to understand the interactions between the ecological, socioeconomic and cultural dimensions of forests and diets.